EFFECT OF E-COMMERCE, PUBLIC RELATIONS AND CUSTOMER RELATIONSHIP MANAGEMENT ON PURCHASE DECISIONS (CASE STUDY OF OPPO BRAND SMARTPHONE USERS IN WTC SURABAYA) - Enny Istanti (LPPM ITB AAS INDONESIA (d.h STIE AAS Surakarta), 2021)
Business competition will look increasingly fierce. With the development of technology, information, communication and knowledge, companies will increasingly realize that the company's goal is no longer how to increase sales volume but is more prioritized on creating customer satisfaction in making purchasing decisions. The population in this study were all visitors to WTC Surabaya. The sample used in this study were 105 respondents. The sampling technique used in this study was accidental sampling. The results of the study that the independent variables consisting of E-Commerce, Public Relations and Customer Relationship Management partially and significantly influence the purchasing decisions of OPPO brand smartphones at WTC Surabaya are accepted and proven. The E-Commerce variable has a dominant influence on purchasing decisions for OPPO brand smartphones at WTC Surabaya, which is accepted and proven. The conclusion of this study is that the independent variables consisting of E-Commerce, Public Relations and Customer Relationship Management have a partial and significant effect on purchasing decisions for OPPO brand smartphones at WTC Surabaya, which are accepted and proven true based on the t count > t table and the significant value is smaller. of 0.005. The E-Commerce variable has a dominant influence on the OPPO smartphone purchase decision at WTC Surabaya has the largest beta coefficient value among the Public Relations and Customer Relationship Management variables.